ISSUES OF SOCIAL PROTECTION OF NATIONAL GUARD SERVICEMEN IN THE CONCEPT OF PUBLIC SECURITY - Gaziev Shakhrukh Murodalievich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2021)
This concept opened up a new era of social protection of employees of internal affairs and National Guard servicemen in Uzbekistan. Paragraph 10 of the decree sets out the task of preparation of government decision projects on specific and complete measures of social protection of National Guard servicemen and internal affairs personnel.